Millimeter, Submillimeter, and Far-Infrared Detectors and Instrumentation for Astronomy IX 2018
DOI: 10.1117/12.2313256
|View full text |Cite
|
Sign up to set email alerts
|

Simulations and performance of the QUBIC optical beam combiner

Abstract: QUBIC, the Q & U Bolometric Interferometer for Cosmology, is a novel ground-based instrument that aims to measure the extremely faint B-mode polarisation anisotropy of the cosmic microwave background at intermediate angular scales (multipoles of = 30 − 200). Primordial B-modes are a key prediction of Inflation as they can only be produced by gravitational waves in the very early universe. To achieve this goal, QUBIC will use bolometric interferometry, a technique that combines the sensitivity of an imager with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…We 2https://www.ticra.com/software/grasp/ Figure 8. CAD model of the beam combiner showing the 3D model of the beams (here coloured yellow pink and green) propagating between the two mirrors [24], [11].…”
Section: Stray-lightmentioning
confidence: 99%
See 1 more Smart Citation

QUBIC VIII: Optical design and performance

O'Sullivan,
De Petris,
Amico
et al. 2020
Preprint
Self Cite
“…We 2https://www.ticra.com/software/grasp/ Figure 8. CAD model of the beam combiner showing the 3D model of the beams (here coloured yellow pink and green) propagating between the two mirrors [24], [11].…”
Section: Stray-lightmentioning
confidence: 99%
“…The focal plane image is sampled by an array of cooled transition-edge sensor (TES) bolometers, hence the term bolometric interferometry. [11]).…”
Section: Contents 1 Introductionmentioning
confidence: 99%

QUBIC VIII: Optical design and performance

O'Sullivan,
De Petris,
Amico
et al. 2020
Preprint
Self Cite
“…The requirement to sample the narrowest fringes (the longest baselines of interest) with two or more 3-mm wide detectors limits the focal length to 300 mm. This short focal length means that aberrations are an issue, but our simulations have shown that they nevertheless only decrease the sensitivity of the instrument by about 6% 19 . The use of reflectors means that the system can be accurately modelled with physical optics (PO) software such as GRASP 20 .…”
Section: The Optical Combinermentioning
confidence: 78%
“…14 detectors will be reported elsewhere, after the calibration of the technological demonstrator is completed. More details on the simulation of the optical beam combiner and horns array can be found in [50].…”
Section: Current Status and Forecastsmentioning
confidence: 99%